Reconceptualising the home economics curriculum for a new South African educational dispensation - Vosloo, M. C.(Marieta Charlyn),1946- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1994.